A facile method for fabricating a three-dimensional aligned fibrous scaffold for vascular application - Ng, Feng Lin (2019)
Vascular graft replacement remains the optimal treatment option for many vascular diseases despite advances in endovascular surgery. In this study, we proposed the use of surface topographical cues to align and maintain the phenotype of vascular smooth muscle cells (vSMCs) which were reported as one of the vital limitations for successful graft replacement. An auxiliary electrospinning setup has been developed to collect circumferentially aligned fibres on a 3D tubular format; this micro-architecture was found to be similar to the tunica media layer of blood vessels. The presence of aligned fibres served as a signaling modality to induce cell alignment and the maintenance of the contractile phenotype. vSMCs cultured on the 3D aligned fibrous substrate were found to exhibit better cell proliferation ability and enhanced cell-shape directionality. The functional expression of the two representative intracellular contractile proteins (i.e. α-SMA and MHC) was found to exhibit definitive markers that are orderly organized as microfilament bundles. Collectively, the result suggests a possibility of adapting the 3D aligned tubular scaffold to enhance and regulate cell function along with the additional tunability of scaffold diameter and thicknesses for tailoring to the needs of individual patients or future ex vivo studies.